Does capital intensity, inventory intensity, firm size, firm risk, and political connections affect tax aggressiveness? - Sugeng, Sugeng; Prasetyo, Eko; Zaman, Badrus (University of Islam Malang, 2020)
Tax aggressiveness is one of a critical issue in the world of taxation. Many companies do tax planning to minimize their tax abilities. This study aims to examine how capital intensity, inventory intensity, firm size, firm risk, and political connections, relate to the tax aggressiveness of manufacturing listed companies in Indonesia, an emerging economy of Southeast Asia. This study combined the tax aggressiveness factor from different perspectives into one model. This study used purposive sampling with manufacturing companies listed in Indonesia Stock Exchange during 2015-2017 and experienced a consecutive profit as the main criteria. Panel data regression used as a data analysis technique. The result shows that there is a significant effect between capital intensity, political connection, and tax aggressiveness. The relationship between inventory intensity, firm size, firm risk, and tax aggressiveness failed to prove in this study. This result is consistent across several measures of tax aggressiveness.